Celebrity Capital and the Issues in Filipino Celebrities’ Political Entry and Expansion into National Elections: The Cases of Isko Moreno and Manny Pacquiao - Manlangit, Adrian Carlo C. (Philippine Social Sciences Review; Vol 75 No 1 (2023): PSSR Vol. 75 No. 1 2023, Ed. Jorge V. Tigno, 2025)
In the Philippines, parties are mere volatile alliances, and nominations are guided mostly by winning prospects. Within this setting, a new breed of politicians has emerged — celebrity politicians. Inexperienced but famous, these media figures have given career and elite politicians a run for their money. Nevertheless, scant studies have been conducted to develop a nuanced theory of when, why, and how they win and the issues in their entry into national politics. Following Driessens (2013) and using the cases of Isko Moreno and Manny Pacquiao, I argue that celebrities successfully penetrate politics because they possess a unique resource — celebrity capital — composed of favorable reputations, symbolic roles, and narratives that, when harnessed strategically, can be converted into legitimacy to combat the tendency to be seen as unfit for office. Nevertheless, as the cases show, celebrity capital has its own limitations and risks which can invite celebrities’ electioneering to eventually converge with that of traditional politicians, casting doubt on their potential to improve the country’s deformed elections. The findings call for a reevaluation of our elections and reforms to make them less personalistic and more programmatic.